Study protocol - resilience in individuals and families coping with the impacts of alcohol related injuries in remote indigenous communities: a mixed method study - West, Caryn (BioMed Central, 2014)
BACKGROUND: Alcohol Management Plans (AMPs) were first implemented by the Queensland Government a decade ago (2002–03). In 2008, further stringent controls were implemented and alcohol was effectively prohibited in some of the affected remote Indigenous communities. With the Queensland Government currently reviewing AMPs, prohibitions may be lifted making alcohol readily available once more in these communities. As yet no work explores the impact of alcohol related injuries in relation to individual, family and community resilience in Indigenous Australians. A resilience model recognises individuals and families for their strengths rather than their deficits. By revealing how some individuals and families survive and thrive, new ways of working with families who need support may be identified and adopted. The research will explore in detail the long-term impact of this kind of injury on individuals, families and communities. METHODS/DESIGN: This project will use a sequential explanatory mixed method design. Four discrete Indigenous communities in Cape York, far north Queensland are included in this program of research, chosen because there is previous data available regarding injury and alcohol related injuries. Four sequential studies will be conducted in order to address the research questions and provide a rich description of the impact of alcohol related injuries and resilience in these populations. The time period January 2006 to December 2011 was chosen because it captures the three years before and three years after 2008 when tight alcohol restrictions were implemented in the four communities. DISCUSSION: Long term effects of the AMPs are as yet unknown and only fragmented attempts to look at the impact of injury related to alcohol have been conducted. A well-structured research program that explores the long-term impact of alcohol related injuries in these communities will help inform policy development to capture the current situation and so that appropriate benchmarking can occur. The project has been approved by the James Cook University Human Research Ethics Committee H5618 & H5241.